Analisis Maslahah Penglibatan Malaysia dalam RCEP serta Implikasi Ekonomi dan Sosial: (Analysing Maslahah in Malaysia's Participation in RCEP and Its Economic and Social Implications) - Nor Azelan, Suffian Haqiem; Ismail, Muhammad; Mohamad, Mohammad Taqiuddin; Zulkepli, Muhammad Izzul Syahmi (Online Journal of Research in Islamic Studies, 2025)
As the world's largest trade agreement involving ASEAN countries and key trading partners such as China, Japan, South Korea, Australia, and New Zealand, RCEP offers various economic benefits to Malaysia, including increased exports, foreign direct investment (FDI), and integration into regional supply chains. However, this trade agreement also presents challenges, particularly in terms of domestic industry competition, effects on small and medium enterprises (SMEs), and social implications. A qualitative research approach is employed in this study, where data is gathered from journal articles, research reports, by Islamic scholars, and official sources related to Malaysia’s participation in international trade agreements. The primary focus of this study is to examine the policies, implementation, and impact of RCEP on Malaysia’s economy and society, as well as its alignment with Maqasid Shariah principles, particularly economic benefits and social protection. The findings indicate that Malaysia's participation in RCEP provides economic advantages such as increased exports, higher FDI, and deeper global supply chain integration. However, challenges remain in terms of domestic industry competition, reliance on external markets, and impacts on SMEs. The maslahah analysis suggests that Shariah-based strategies should be adopted to ensure a balance between economic benefits and social needs, such as worker protection, environmental sustainability, and economic stability. Therefore, this study provides a clearer understanding of the economic and social implications of Malaysia’s participation in RCEP and serves as a reference for policymakers and Islamic financial institutions in formulating more sustainable and Shariah-compliant trade strategies.